Transformasi Digital Komunikasi Pemasaran. Strategi Meningkatkan Penjualan Produk Usaha Kecil Menengah (UKM) dalam Pemasaran Digital. Studi Pada Produk Maicih Bandung - Harningsih, Harningsih; Andayani, Lies; Siregar, Rachmi Kurnia; Alamsyah, Alamsyah (CAKRAWALA: JURNAL HUMANIORA BINA SARANA INFORMATIKA, 2025)
Digital transformation has become an essential need in facing the dynamics of the global economy and the changing behavior of today’s consumers. Through digitalization, SMEs can reach wider markets, accelerate production and distribution processes, and strengthen customer relationships. Maicih has successfully built a strong brand through product innovation and creative marketing strategies. This study aims to analyze how digital transformation is applied in Maicih Bandung’s marketing communication strategy and its impact on increasing sales. The approach used is qualitative descriptive with a case study method, to deeply explore marketing strategies through digital media, the use of reseller networks, and distribution via modern retail (supermarkets). Research findings: Through SWOT analysis, it can be seen that Maicih intensively utilizes social media, particularly TikTok, with live streaming up to 10 hours per day as a form of interactive and real-time promotion. The hybrid distribution strategy through reseller communities and supermarkets provides wider market reach while strengthening brand positioning in the national market. The marketing strategy employed is integrated with multiple components, forming a unified whole through the concept of Integrated Marketing Communication (IMC), involving synergy between content, interaction, and direct sales. It can be concluded that a consistently and adaptively implemented digital transformation can maintain competitiveness and sustain business existence in order to increase sales volume. Partnering with resellers and collaborating with retail supermarkets becomes the main strategy in maintaining customer loyalty.